Penerapan public relation dalam pelayanan konsumen di "Takoyaki Takokoki" - Hakiki, Mohamad Fahmi (Maliki Interdisciplinary Journal, 2024)
This study focuses on the "Takoyaki Takokoki" branch on Jalan Surabaya and applies public relations theory in customer service. Public relations studies focus on two-way communication with the aim of creating good relationships between organizations and society. The researcher also acted as a salesperson during three days of observation at the sales stand. The research results show that there are problems with the manual queuing system, cash payments and manual ordering. To overcome this problem, queue management, cash exchange, and double-checking of orders are carried out before they are given to buyers. This study discusses the problems faced by Public Relations when implementing it and provides a perspective on strategies to improve public services.